Determinants of TARGET2 transactions of European banks based on micro-data - Constantin Drott; Stefan Goldbach; Axel Jochem (Deutsche Bundesbank, 2022)
This paper examines German and foreign bank factors that can explain cross-border central bank liquidity flows between Germany and the rest of the euro area. Using data from the German component of Eurosystem's real-time gross settlement system TARGET2 and BankFocus for the period between 2009 and 2021, we provide empirical evidence that only few balance sheet items and profit and loss accounts affect flows with Germany. We control for bilateral bank-specific relationships and time-varying macroeconomic country effects in our regressions. In general, German bank factors seem to be more important than characteristics of foreign banks. A German bank that exhibits relatively high claims against a central bank seems to attract less additional central bank liquidity from abroad than a German bank with fewer existing central bank claims. However, higher overall liquidity of a German credit institution corresponds to additional net inflows. Foreign bank factors only matter for central bank payments and intragroup payments. We also document heterogeneities across different types of transactions which influence the German TARGET2 balance. While customer payments, interbank payments and central bank payments have increased net flows to Germany in sum, intragroup payments and ancillary systems' transactions have led to net outflows.
Keywords: F3; F32; G15; 330; Capital flows; TARGET2 transactions; central bank liquidity